Diagnostic challenges in cutaneous leishmaniasis due to atypical Leishmania infantum: pathologists’ insights from re-emergence zones - Ekemen, Suheyla; Nalcaci, Muhammed; Toz, Seray; Sanjoba, Chizu; Demirkesen, Cuyan; Cetin, Emel D.; Tecimer, Tulay; Yildiz, Pelin; Gursel, Mayda; Ince, Umit; Ozbel, Yusuf; Coban, Cevayir (Frontiers in Medicine, 2024)
Background: Leishmaniasis, a parasitic infection affecting both humans and animals, is increasingly spreading across Mediterranean and European regions, largely driven by human migration and environmental changes. In countries like Turkey and across Europe, which have seen large influxes of migrants, the incidence of cutaneous leishmaniasis (CL) is rising, with cases now appearing in cities where the disease was previously undocumented. In these previously non-endemic areas, physicians unfamiliar with the characteristic lesions may misdiagnose CL, particularly in cases with only cutaneous manifestations. This study aims to evaluate the impact of re-emerging CL on the routine diagnostic practices of pathologists in Turkey, by retrospectively reviewing cases. We conducted a retrospective analysis of CL cases diagnosed between 2013 and 2022 at a single pathology center in Turkey, covering multiple provinces. Twelve cases of CL were identified and analyzed based on clinical presentation, pre-diagnosis, histopathological findings, and molecular diagnostics. DNA extraction and PCR were performed on paraffin-embedded tissue samples to identify the Leishmania species involved.Results: Out of the twelve CL cases reviewed, seven exhibited morphological findings strongly suggestive of CL (MFSS of CL), warranting further microbiological evaluation. All patients presented with non-healing skin lesions characterized by central ulceration, crater-like formations, or papulonodular lesions. Notably, CL was included in the clinical pre-diagnosis in only 58.3% of cases, while it was not considered in the remaining 41.7% of cases. Clinicians initially pre-diagnosed skin tumors in six cases (50%), four of which led to wide surgical excision. Histopathological examination in all cases revealed chronic or mixed (acute/chronic) inflammation, predominantly rich in histiocytes. To further investigate the role of Leishmania species in the pre-diagnosis, DNA extraction and PCR were performed on paraffin-embedded tissue samples, identifying L. infantum as the causative agent in ten cases and L. major in two cases. Notably, L. infantum was the causative agent in all five cases initially misdiagnosed as skin tumors, which were also associated with a granulomatous type of chronic inflammation.This study highlights the diagnostic challenges in distinguishing CL from skin tumors, particularly in non-endemic regions where L. infantum is an atypical causative agent.